1998
DOI: 10.1097/00006534-199802000-00045
|View full text |Cite
|
Sign up to set email alerts
|

Practical Precautions for Avoiding Sharp Injuries and Blood Exposure

Abstract: Current surgical practices result in greater than a 50-percent incidence of blood exposure per operation for surgeons and operating team members who do not take any added precautions during their procedures. By incorporating changes in personal exposure protection, double gloving, and developing safer techniques during operations, it is estimated that the exposure risk to blood and body fluids can be decreased among surgeons by 74 percent. This article reviews practice precautions that may be acquired by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…A striking result was that up to 21% of the glove failures were undetected until the moment the gloves were taken off. Though lower than in previous studies, which have indicated that the surgeon is unaware the glove is perforated in more than 50% of such occurrences [18,21,23,26,27], particular concern remains over occult blood exposure through intimate skin contact for lengthy periods of time [28].…”
mentioning
confidence: 60%
“…A striking result was that up to 21% of the glove failures were undetected until the moment the gloves were taken off. Though lower than in previous studies, which have indicated that the surgeon is unaware the glove is perforated in more than 50% of such occurrences [18,21,23,26,27], particular concern remains over occult blood exposure through intimate skin contact for lengthy periods of time [28].…”
mentioning
confidence: 60%
“…4 Smoot reported that "most students indicate that they do not see routine universal precautions undertaken by staff and residents, and no requirement for the compliance is enforced". 28 Around 60% of NSIs were not reported by dental students. Non-reporting of NSIs is a contentious issue within the dental profession the most common reason for that was the student's lack of knowledge that all injuries had to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…One study has also suggested that double gloving offers protection against skin contamination in microsurgical procedures (Hentz et al, 2001). A comfortable method of latex double gloving consists of wearing a one half-size larger than the normal inner glove, with a normal glove as the second layer (Smoot, 1998). Wearing indicator gloves allows the wearer to detect perforations to the outer gloves more easily (Tanner and Parkinson, 2004).…”
Section: Hand Protectionmentioning
confidence: 99%
“…It is safer to ''instrument tie'' suture knots. It is also advisable to avoid tying knots with short suture lengths when the needle is still attached, as this may result in a needle puncture of the palm (Smoot, 1998).…”
Section: Surgical Techniquementioning
confidence: 99%